2018
DOI: 10.1186/s13662-018-1603-1
|View full text |Cite
|
Sign up to set email alerts
|

Existence and numerical solutions of a coupled system of integral BVP for fractional differential equations

Abstract: This paper is devoted to establishing the existence theory for at least one solution to a coupled system of fractional order differential equations (FDEs). The problem under consideration is subjected to movable type integral boundary conditions over a finite time interval. Furthermore, we investigate the approximate solutions to the considered problem with the help of the differential transform. Moreover, some necessary conditions for the Hyers-Ulam type stability to the solution of the proposed problem are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Fractional type operators are a class of important operators in harmonic analysis and were widely used in the study of partial differential equations and function spaces [1, 2, 4–6, 9, 15, 20, 22, 30]. Recall that the fractional maximal function Mα and the fractional integral operator Iα are defined by Mαffalse(xfalse):=trueprefixsupQx1false|Qfalse|1α/nQfalse|ffalse|,0<α<n,and Iαffalse(xfalse):=Rnf(y)false|xyfalse|nα,0<α<n,respectively, where f is a locally integrable function defined on Rn and Q takes over all cubes in Rn which contain x .…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…Fractional type operators are a class of important operators in harmonic analysis and were widely used in the study of partial differential equations and function spaces [1, 2, 4–6, 9, 15, 20, 22, 30]. Recall that the fractional maximal function Mα and the fractional integral operator Iα are defined by Mαffalse(xfalse):=trueprefixsupQx1false|Qfalse|1α/nQfalse|ffalse|,0<α<n,and Iαffalse(xfalse):=Rnf(y)false|xyfalse|nα,0<α<n,respectively, where f is a locally integrable function defined on Rn and Q takes over all cubes in Rn which contain x .…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…Furthermore, the study of fractional systems has also been a topic focused on; see [19][20][21][22][23][24][25]. Although the coupled systems of fractional boundary value problems have been considered by some authors, coupled systems with multi-order fractional orders are seldom discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Although the coupled systems of fractional boundary value problems have been considered by some authors, coupled systems with multi-order fractional orders are seldom discussed. The orders of the nonlinear fractional systems which are considered in the existing papers belong to the same interval (n, n + 1] (n ∈ N + ); see [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In the present research work, the CWM is fully compatible with the complexity of the problems and has shown extremely accurate results, especially in case of fractional linear and nonlinear boundary problems of fourth, sixth and eighth order [21][22][23][24][25][26][27]. Some other well -known methods for the solution of fractional differential equations are given in [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%